Plantas de cobertura de verão: crescimento e acúmulo de nutrientes, épocas de dessecação e produtividade do trigo - Link, Lucas (2020)
More than 2 million hectare of cultivated soil at the maize/soybean-wheat offseason remains on fallow in Brazil. Therefore, this research studied a suitable cover crop considering its biomass accumulation, nutrient cycling and its herbicide management to be adopted in this period as well as its influence on wheat yield at the 2017/18 and 2018/19 growing season. Experiment was carried out at the UTFPR Câmpus Dois Vizinhos and was laid out as a randomized block design in a factorial scheme with four replications. Maize/wheat offseason was composed of five cover crops (Fagopyrum esculentum, Crotalaria juncea, Pennisetum glaucum, Urochloa brizantha and Crotalaria spectabilis at 2017/18 growing season and at 2018/19, Fagopyrum esculentum and Crotalaria spectabilis were switched for Dolichos lablab). Soybean/wheat offseason was composed of four cover crops (Fagopyrum esculentum, Crotalaria juncea, Pennisetum glaucum, and Urochloa brizantha). Both experiments used two herbicide management (Desiccation 17 days before and at the wheat sowing day). Fallow was used as a control. All the studied cover crops showed a good biomass yield potential and can be used in the maize/soybean-wheat intercrop with certain specificities. F. esculentum showed the fastest development cycle and suits well at shorter offseason periods, with 50 days of length. Its herbicide management at the wheat sowing day shows better results, once its seed yield may result in competition later on with wheat. C. juncea showed higher yield than C. spectabilis, eaching dry matter values up to 3,800 kg ha-1. Crotalarias showed a linear increase in biomass along the periods without wheat yield effects and its herbicide dissection at the wheat sowing day is recommended. P. glaucum showed the highest biomass yield at both years and summer crops (maize and soybean), standing out as the best option for offseason periods of 70 to 80 days. U. brizantha is a potential species, but for periods longer than 70 days. Tradeoff between the additional biomass produced by millet and brachiaria between herbicide desiccation periods does not pay the wheat grain yield reduction, suggesting that its herbicide management should be anticipated. Further studies should consider other cover crop benefits as weed suppression, physical and chemical soil traits and erosion reduction.